2013
DOI: 10.1097/mcg.0b013e31828b288a
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection and Inflammatory Bowel Disease

Abstract: The prevalence of Clostridium difficile infection (CDI) in inflammatory bowel disease (IBD) has become a focus of increased attention, as the C. difficile epidemic continues to grow. Although first documented more than 20 years ago, only in recent years has the relationship between these 2 entities been better clarified, and recent epidemiologic studies have shown that IBD patients are at increased susceptibility for CDI compared with the general population. Despite this increased attention, much still remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 64 publications
0
22
0
2
Order By: Relevance
“…The recurrence rate may be as high as 25% within 30 days after metronidazole or vancomycin treatment [84,85]. The symptomatic presentations of CDI and IBD are hardly distinguishable (diarrhea, leukocytosis, hypoalbuminemia, and fever) [86,87], and so poses difficulty for pinpoint therapy. Evidence is accumulating on the linking of CDI with IBD flares and relapses, as indicated by 5% to 60% toxin positive rates in the latter [86].…”
Section: Pathogenic Bacteria Associated With Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate may be as high as 25% within 30 days after metronidazole or vancomycin treatment [84,85]. The symptomatic presentations of CDI and IBD are hardly distinguishable (diarrhea, leukocytosis, hypoalbuminemia, and fever) [86,87], and so poses difficulty for pinpoint therapy. Evidence is accumulating on the linking of CDI with IBD flares and relapses, as indicated by 5% to 60% toxin positive rates in the latter [86].…”
Section: Pathogenic Bacteria Associated With Ibdmentioning
confidence: 99%
“…The symptomatic presentations of CDI and IBD are hardly distinguishable (diarrhea, leukocytosis, hypoalbuminemia, and fever) [86,87], and so poses difficulty for pinpoint therapy. Evidence is accumulating on the linking of CDI with IBD flares and relapses, as indicated by 5% to 60% toxin positive rates in the latter [86]. Incidence of CDI is 2.9-, 4.0-, and 2.1-fold of non-IBD controls for IBD, UC and CD patients respectively [88].…”
Section: Pathogenic Bacteria Associated With Ibdmentioning
confidence: 99%
“…Due to the high prevalence of CDI in IBD patients and clinical/laboratory similarity between CDI and IBD exacerbation, it is recommended that all IBD patients with a disease flare should be tested for C. difficile (14)(15)(16)(18)(19)(20)(21). There is no indication for post-treatment testing to confirm cure.…”
Section: Diagnosismentioning
confidence: 99%
“…CDI was first associated with IBD in the early 1980s (13), but was somehow neglected until ten years ago, when several studies and reviews clearly demonstrated that patients with one of the two major forms of IBD (ulcerative colitis-UC; Crohn's disease-CD) are at high-risk for CDI (8)(9)(10)(11)(12)(14)(15)(16)(17)(18)(19)(20)(21). Besides the well-known risk factors for CDI in non-IBD population, there are some typical IBD-related risk fac-EPIDEMIOLOGY Both single-center studies (8,9,22,27,(29)(30)(31) and large nationwide data analyses (9,11,12,26) have independently reported an increased CDI incidence among IBD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for worsening of preexisting IBD after liver transplant includes active bowel inflammation at the time of transplantation [193], short interval between diagnosis of IBD and transplant [193], cigarette smoking [197], Clostridium difficile infection [198] and use of Tacrolimus after transplant [191,193,199,200]. The use of steroid or immunosuppressive agents prior to transplant does not predict post-transplant IBD activity [194,195].…”
Section: Ibd and Liver Transplantationmentioning
confidence: 99%